THE STRUGGLE OF SCARLET O’HARA TO FIND PURE LOVE IN MARGARET MITCHEL’S GONE WITH THE WIND (1936) - Eli Diana (Literary Criticism, 2015)
This research is entitled The Struggle of Scarlet O’hara to Find Pure Love in Margaret Mitchel Gone With The Wind (1936). The aim of the study is exploring  the most dominat needs of Scarlet O’hara needs appering in Gone With The Wind (1936) and to know the struggles of Scarlet O’hara in finding her needs in Gone With The Wind (1936). This research used a qualitative method to explore the protagonist character in the novel and used the concept of Abraham Maslow’s using five basic hierarchy of needs especially focused on the struggle for love, affection and belongingness also self actualization needs. Based on the analysis, the researcher found that Scarlet O’hara struggles to love, affection, belongingness and self actualization because she needs a man to love, family’s affection and get many friends. The finding of this research revealed that the most dominant needs of Scarlet O’hara  appering   in Gone With The Wind (1936) is the needs of love, affection, and belongingness to make her life full of joys and happiness.Keywords : Struggle, Love, Affection, Belongingness